Ferrate(VI)-induced arsenite and arsenate removal by in situ structural incorporation into magnetic iron(III) oxide nanoparticles - Prucek, Robert; Tuček, Jiří; Kolařík, Jan; Filip, Jan; Marušák, Zdeněk; Sharma, Virender K; Zbořil, Radek (Environmental science & technology, 2013)
We report the first example of arsenite and arsenate removal from water by incorporation of arsenic into the structure of nanocrystalline iron(III) oxide. Specifically, we show the capability to trap arsenic into the crystal structure of γ-Fe2O3 nanoparticles that are in situ formed during treatment of arsenic-bearing water with ferrate(VI). In water, decomposition of potassium ferrate(VI) yields nanoparticles having core-shell nanoarchitecture with a γ-Fe2O3 core and a γ-FeOOH shell. High-resolution X-ray photoelectron spectroscopy and in-field (57)Fe Mössbauer spectroscopy give unambiguous evidence that a significant portion of arsenic is embedded in the tetrahedral sites of the γ-Fe2O3 spinel structure. Microscopic observations also demonstrate the principal effect of As doping on crystal growth as reflected by considerably reduced average particle size and narrower size distribution of the "in-situ" sample with the embedded arsenic compared to the "ex-situ" sample with arsenic exclusively sorbed on the iron oxide nanoparticle surface. Generally, presented results highlight ferrate(VI) as one of the most promising candidates for advanced technologies of arsenic treatment mainly due to its environmentally friendly character, in situ applicability for treatment of both arsenites and arsenates, and contrary to all known competitive technologies, firmly bound part of arsenic preventing its leaching back to the environment. Moreover, As-containing γ-Fe2O3 nanoparticles are strongly magnetic allowing their separation from the environment by application of an external magnet.
Keywords: arseničnany; fotoelektronová spektroskopie; velikost částic; Kinetics; Hydrogen-Ion Concentration; teplota; železo; Photoelectron Spectroscopy; Particle Size; arsen; Magnetite Nanoparticles; krystalografie rentgenová; spektroskopie Mossbauerova; Temperature; Iron; Arsenites; Arsenic; Arsenates; Crystallography, X-Ray; magnetické nanočástice; koncentrace vodíkových iontů; kinetika; arsenitany; Spectroscopy, Mossbauer